NOVEL USE OF WASTE KERATIN AND COTTON LINTER FIBERS FOR PROTOTYPE TISSUE PAPERS AND THEIR EVALUATION - Bo Shi; Tom G. Shannon; Ellen Pelky (BioResources, 2010)
Corporate environmental sustainability calls for sustainable product manufacturing with less creation of waste material or increased reuse of waste materials. One example is the use of keratin fiber from the poultry industry and cotton linter from the textile industry for paper and tissue manufacturing. In this paper, the feasibility of using these waste fibers to make paper was demonstrated in handsheets. The properties of these handsheets were compared to the properties of handsheets made with standard bleached eucalyptus tropical hardwood fibers. A blend of cotton linter and keratin fibers at 80/20 and 60/40 ratios showed a 59% and 73% improvement in sheet bulk, respectively, compared to eucalyptus handsheets. Similarly, air permeability of the cotton / keratin fiber handsheets improved 414% and 336%, respectively, versus the eucalyptus. However, the tensile index of the cotton and keratin fiber blends was lower than the eucalyptus sheets. There was no remarkable difference in water absorbency up to 20% keratin fiber. Above 20% of keratin fibers the water absorbency started to decrease, which is likely attributable to the hydrophobic nature of the protein-based keratin fiber.